PENGEMBANGAN BUKU AJAR MENULIS MELALUI ANALISIS KESALAHAN (FEHLERANALYSE BEIM SCHREIBEN) DAN INTEGRASI PENDIDIKAN KARAKTER - Sahat Perdamean, Ahmad; Kurnia Sari, Tanti (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This research aims to develop the textbook course Schreibfertigkeit IV through error analysis and integrating of character education in learning. Research subject is students who followed courses Schreibfertigkeit IV study program in German language, FKIP HKBP Nommensen Pematangsiantar and FBS Universitas Negeri Medan. The instruments used are: validation instrument of the content of textbook, lecturers response instrument, students response instrument to the textbook course, instruments observation lecturer activities, instrument observation student activities, test and documentation. Data were analized with presentation technique. The result showed, that the textbook was developed in accordance with the procedures described, has good quality because it is valid, practical and effective. The use textbook improve students learning outcomes and also create the values of good character.